FAKTOR YANG MEMPENGARUHI PENDAPATAN PENDUDUK MISKIN DI KAWASAN BALI TIMUR PROVINSI BALI - Sari, Ni Ketut Widya Purnama; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Poverty becomes a problem in economic development that inhibits the creation of a just, prosperous and equitable life in accordance with the goals of each country. The research objectives are to analyze the effect of work participation of family members, the type of work and the role of community perceptions of poverty conditions in moderating the types of work to the incomes of the poor. In this study used primary data with non-participant observation, structured interviews and in-depth interviews and with the classic assumption test analysis technique, significant test and moderation regression analysis. The results of the analysis show that work participation of family members has a significant positive effect on the income of the poor in the East Bali Region, the poor in the East Bali Region who have formal jobs get higher income per household compared to the poor who have informal jobs, and the community perception variable about significant poverty conditions and weaken the effect of types of work on the income of the poor in the East Bali Region. Keywords : income of poor people, work participation of family members, type of work, community perception of poverty conditions.